2013
DOI: 10.1186/1471-2490-13-58
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns and characteristics of European patients with castration-resistant prostate cancer

Abstract: BackgroundEuropean treatment guidelines recommend the use of hormonal therapy for the treatment of advanced prostate cancer, including castration-resistant prostate cancer (CRPC), but there is little understanding of how common practices in prostate cancer treatment compare across Europe. The aim of this analysis was to evaluate the management of CRPC patients across five European countries (France, Germany, Italy, Spain and the UK).MethodsData were drawn from the Adelphi Real World Prostate Cancer Disease Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 14 publications
0
38
0
2
Order By: Relevance
“…Baseline characteristics of patients in this study were also similar to those of patients with CRPC across five European countries (France, Germany, Italy, Spain, and the United Kingdom) 31 . Most patients in the European study were elderly, with a mean age of 71 years and mean of 1.8 comorbidities, most frequently hypertension (65.6%) and diabetes (31.7%); with bone the most common site of metastases.…”
Section: Discussionmentioning
confidence: 89%
“…Baseline characteristics of patients in this study were also similar to those of patients with CRPC across five European countries (France, Germany, Italy, Spain, and the United Kingdom) 31 . Most patients in the European study were elderly, with a mean age of 71 years and mean of 1.8 comorbidities, most frequently hypertension (65.6%) and diabetes (31.7%); with bone the most common site of metastases.…”
Section: Discussionmentioning
confidence: 89%
“…The American Society of Clinical Oncology and NCCN recommend that ADT should be continued indefinitely in the setting of mPC despite the development of castration resistance 9,73 . But a survey of PC physicians from five European countries (France, Germany, Italy, Spain, and the United Kingdom) found that up to one third of physicians used chemotherapy as a monotherapy and stopped administering ADT after the development of castration resistance 74 . The panel did not endorse discontinuing ADT after emergence of castration‐resistant disease.…”
Section: Resultsmentioning
confidence: 99%
“…5 Cross-sectional survey data from 3,477 patients with CRPC in five countries (France, Germany, Italy, Spain and the UK) revealed that between 19% and 45% (in the UK and Italy, respectively) of patients received chemotherapy alone with no ADT (Figure 1). The reasons for this divergence between guidelines and clinical practice are unclear, and this study reported no consistent link between years of practice and likelihood of continuing ADT in CRPC 5. However, this apparent tendency for some clinicians to overlook the need for continued ADT may expose patients to unnecessary risk.…”
Section: Adherence To Guidelinesmentioning
confidence: 99%
“…A 6-month retrospective study of 73 men with non-mPCa found that any recorded testosterone peak above 1.1 nmol/L (32 ng/dL) was associated with significantly impaired survival free of androgen independent progression (88 months [95% CI, 55–121] versus 137 months [95% CI, 104–170], respectively; P <0.03) 11. In addition, rising PSA levels are commonly used to diagnose CRPC in the clinic, with a minority of oncologists or urologists citing testosterone levels as an additional marker, according to a European survey 5. Clinical trials have continued to use the <1.7 nmol/L testosterone cutoff, although some studies are starting to explore lower cutoff values 12.…”
Section: Defining Medical Castration With Adtmentioning
confidence: 99%
See 1 more Smart Citation